A Randomized Controlled Trial of Postoperative Thoracic Epidural Analgesia Versus Intravenous Patient-controlled Analgesia After Major Hepatopancreatobiliary Surgery. Issue 3 (September 2017) - Aloia, Thomas A.; Kim, Bradford J.; Segraves-Chun, Yun Shin; Cata, Juan P.; Truty, Mark J.; Shi, Qiuling; Holmes, Alexander; Soliz, Jose M.; Popat, Keyuri U.; Rahlfs, Thomas F.; Lee, Jeffrey E.; Wang, Xin Shelley; et al.
Abstract : Objectives: The primary objective of this randomized trial was to compare thoracic epidural analgesia (TEA) to intravenous patient-controlled analgesia (IV-PCA) for pain control over the first 48 hours after hepatopancreatobiliary (HPB) surgery. Secondary endpoints were patient-reported outcomes, total narcotic utilization, and complications. Background: Although adequate postoperative pain control is critical to patient and surgeon success, the optimal analgesia regimen in HPB surgery remains controversial. Methods: Using a 2.5:1 randomization strategy, 140 patients were randomized to TEA (N = 106) or intravenous patient-controlled analgesia (N = 34). Patient-reported pain was measured on a Likert scale (0–10) at standard time intervals. Cumulative pain area under the curve was determined using the trapezoidal method. Results: Between the study groups key demographic, comorbidity, clinical, and operative variables were equivalently distributed. The median area under the curve of the postoperative time 0- to 48-hour pain scores was lower in the TEA group (78.6 vs 105.2 pain-hours, P = 0.032) with a 35% reduction in patients experiencing ≥7/10 pain (43% vs 62%, P = 0.07). Patient-reported outcomes and total opiate use further supported the benefit of TEA on patient experience. Anesthesia-related events requiring change in analgesic therapy were comparable (12.2% vs 2.9%, respectively, P = 0.187). Grade 3 or higher surgical complications (6.6% vs 9.4%), median length of stay (6 days vs 6 days), readmission (1.9% vs 3.1%), and return to the operating room (0.9% vs 3.1%) were similar (all P > 0.05). There were no mortalities in either group. Conclusions: In major HPB surgery, TEA provides a superior patient experience through improved pain control and less narcotic use, without increased length of stay or complications.